Rethinking the Music Business
X, 260 p. 37 illus., 34 illus. in color.
Keywords: COVID-19 had a global impact on health, communities, and the economy. As a result of COVID-19, music festivals, gigs, and events were canceled or postponed across the world. This directly affected the incomes and practices of many artists and the revenue for many entities in the music business. Despite this crisis, however, there are pre-existing trends in the music business – the rise of the streaming economy, technological change (virtual and augmented reality, blockchain, etc.), and new copyright legislation. Some of these trends were impacted by the COVID-19 crisis while others were not. This book addresses these challenges and trends by following a two-pronged approach: the first part focuses on the impact of COVID-19 on the music business, and the second features general perspectives. Throughout both parts, case studies bring various themes to life. The contributors address issues within the music business before and during COVID-19. Using various critical approaches for studying the music business, this research-based book addresses key questions concerning music contexts, rights, data, and COVID-19. Rethinking the music business is a valuable study aid for undergraduate and postgraduate students in subjects including the music business, cultural economics, cultural management, creative and cultural industries studies, business and management studies, and media and communications. .